A participaÁ§ão de Eunice Katunda no Curso Latinoamericano de Música Contemporánea n. 8: desafios e possibilidades (Cuadernos de Análisis y Debate sobre Músicas Latinoamericanas Contemporáneas, 2021)
This article reflects on the participation of Brazilian composer and pianist Eunice Katunda in the eighth edition of Latin American Courses on Contemporary Music (CLAMC), held in Brazil in 1979 in honor, mainly, of the 40 years of the Música Viva group of composers. Created in 1939 by Hans-Joachim Koellreutter, this group was pioneer in disseminating modern compositional techniques in the 1940s in Brazil, being Eunice Katunda one of the members who most national and international pieces of work premiered. In addition to publicizing her own compositions and those of colleagues, Eunice also performed as editor on texts and reviews about musical aesthetics, also in the Música Viva”Ÿs bulletins and in Brazilian newspapers with wide circulation. This fact put her in evidence among the controversy about dodecaphonism in Brazil, culminating not only in her image”Ÿs erosion, but also in the gradual dissolution of the group itself. In this context, the CLAMC”Ÿs eight edition was an opportunity to reconnect her with old colleagues in the musical field, including her master Koellreutter, to whom she publicly apologized. From that moment on, new possibilities opened up for the pianist and composer, who turned to the stages with unpublished works and showing great artistic maturity.
Keywords: Cursos Latinoamericanos de Música Contemporánea; Eunice Katunda; Hans-Joachim Koellreutter; Música Viva group; Latin American Music; Latin American Woman Composer